La presse et ses passeurs méconnus, intermédiaires indispensables à la circulation de la littérature américaine en France dans les années 1940 - Anne Cadin (Transatlantica)
The French press was a crucial intermediary for the circulation of US literature in France during the 1940s. However, its role in this importing process has rarely been studied. Yet, the study of some forty journals (Combat, La Bataille, Action, Carrefour, Esprit...) confirms the construction of a “French taste” in American literature and suggests that the praise of American literary contributions was quickly criticized in periodicals with quite different editorial lines. Furthermore, it is in the press that some unknown mediators forged a critical discourse about a foreseeable influence of US texts on French writers: they were academics (Las Vergnas, Sigaux, Larnac), demanding aficionados (Beaumont, Blanzat, Fauchery, Hoog, Lalou, Morel), but also detractors of this importation (Henriot, Kanapa). The massive arrival of American literature in France did not create an ephemeral fever in the media. On the contrary, the French press scrutinized this American literary “moment” and addressed some fundamental questions, such as the reality of the American literary input or the advent of a literary massification caused by American influence.